Kebijakan Kriminalisasi Pelaku Pemalsuan Uang di Indonesia - Brahmantya Pujalaksa Andhisa; Ifadah Pratama Hapsari (UNES Law Review, 2023)
Abstract: Recently, criminalization has been rampant in Indonesia. One of the actions is counterfeiting money, namely counterfeiting, storing, circulating, importing, selling, spending and so on. The purpose of this research is to inform about criminal threats for perpetrators of money counterfeiting. The method used in this research uses normative juridical with a conceptual and statutory approach as well as a case approach. It can be concluded that this discussion addresses society's problem with counterfeit money. The existence of a policy in Article 36 paragraph 3 in conjunction with Article 26 paragraph 3 of the Law of the Republic of Indonesia Number 7 of 2011 concerning Currency provides more sanctions.